Yahoo Web Search

  1. Ad
    related to K.C
  1. Sort by

  1. (x - h)^2 + (y - k)^2 = r^2 (6 - h)^2 + (5 - k)^2 = r^2 (-3 - h)^2 + (2 - k)^2 = r^2 (-2 - h)^2 + (1 - k)^2 = r^2 (6 - h)^2 + (5 - k)^2 = (-3 - h...6k = 0 48 - 18 - 6k = 0 30 - 6k = 0 6k = 30 k = 30/6 k = 5 (6 - 1)^2 + (5 - 5)^2 = r^2...

    2 Answers · Science & Mathematics · 09/09/2019

  2. ... and 2 points. Set up a system of equations, solve for c and k, then find T(0) 415 = 75 + c * e^(-10k) 340 = c * e^(-10k) 347 = 75 + c * e^(-20k...

    2 Answers · Science & Mathematics · 04/09/2019

  3. (a) domain of f (-∞, ∞) (b) range of f [-1,∞) (c) x-intercepts : 2 and 4 (d) y-intercept : 8 (e) f ...at x=3 (i) the relative minimum of f is -1 (j) f(-4) = 8 (k) The values of x for which f(x)=3 are 1...

    2 Answers · Science & Mathematics · 06/09/2019

  4. ...' is b The distance from (h , k) to C and C' is c (x - h)^2 + (y - k)^2...5 (4.5 , 4.5) is the center of rotation. h^2 + k^2 = a^2 4.5^2 + 4.5^2 = a^2 2 * 4.5^2 = a^2 4.5...

    2 Answers · Science & Mathematics · 18/08/2019

  5. ...b Here are a few other examples: c = kd <-- c varies directly as d e = k/√f <-- e varies inversely as the square root of f. m = kn/...

    4 Answers · Science & Mathematics · 17/08/2019

  6. ... has detailed this approach. Each term is C(n,k) * a^(n-k) * b^k a = x b = -4 Term 0: C(4,0) * x^4 * (-4)^0 -->...

    9 Answers · Science & Mathematics · 16/08/2019

  7. ... = pi*h*r^2 => dV/dt = pi*r^2 dh/dt or in this case 9*pi dh/dt. (c) dV/dt = k*h^(1/2) => k = (-2) / sqrt(16) = -1/2. 9*pi dh/dt = (-1/2)*h^(1/2) => 18*pi...

    2 Answers · Science & Mathematics · 11/08/2019

  8. ...C_atm is the atmospheric concentration, we would model this as: dC(t)/dt = -k*(C(t) - C_atm) where k is some positive rate constant. Note that the...

    2 Answers · Science & Mathematics · 06/08/2019

  9. (A) 20 = 200(1 - e^(-5k)) => 9/10 = e^(-5k) => ln(10/9) = 5k => k = 0.02107. (B) L = 200(1 - e^(-0.2107)) = 38. (C) 180 = 200(1 - e^(-0.02107 t)) => 1/10 = e^(-0.02107 t) => ln(10) = 0.02107 t => t = 109 minutes.

    1 Answers · Science & Mathematics · 28/07/2019

  10. ...and b subscript k which might be part of your confusion. You want to show c(k) = 4c(k-1) 4c(k-1) = 4(2^(k-1) -1) = [2^(k+1)] - 4 (A) Now 2^(k...

    1 Answers · Science & Mathematics · 25/07/2019

  1. Ad
    related to K.C
  1. Try asking your question on Yahoo Answers